Assessment of Basic Ankle Arthroscopy Skills in Orthopedic Trainees. (February 2020) - Johnson, Jeremiah D.; Cheng, Christopher; Schmidtberg, Brian; Cote, Mark; Geaney, Lauren E.
Background: There is increasing emphasis on assessing resident competency, but little has been published on how to best evaluate trainee competency for ankle arthroscopy. The purpose of this study was to validate an objective model for assessing basic ankle arthroscopy knowledge and operative skills on a cadaveric ankle. Methods: The Diagnostic Ankle Arthroscopy Skills Scoring System was adapted from previously validated assessment tools for knee arthroscopy. The scoring system included (1) an oral questionnaire (0-23 points), (2) an operative task-specific checklist (0-19 points), and (3) a global operative skills rating (12-60 points). Thirty-three trainees consisting of orthopedic residents and medical students performed a diagnostic ankle arthroscopy on a cadaveric ankle and were assessed by a single observer, while a subset were tested by 2 evaluators to determine interobserver reliability. Results: There was strong correlation between educational level and scores on the global operative skills rating scale ( r = 0.967, P < .0001), task-specific checklist ( r = 0.815, P < .815), and oral questionnaire ( r = 0.896, P < .0001). The global operative skills scores significantly improved with training level, and the largest difference was between medical students and senior residents. The most notable year-to-year increases in skill were between postgraduate year (PGY) 1 and 2 ( P < .01) and between PGY2 and PGY3 ( P < .05). Oral questionnaire and task-specific checklists were significantly lower for medical students than PGY1 residents ( P < .001). There was also significant improvement in the oral questionnaire between senior and junior residents ( P < .05). There was a moderate correlation between number of self-reported ankle arthroscopy cases and scores on the global operative skills score ( r = 0.7019, P < .0001). Interobserver reliability was high for the global operative skills scores (interclass correlation coefficient = 0.89). Conclusion: The study revealed a valid measure to objectively assess trainees' ankle arthroscopy clinical knowledge and operative skills in a bioskills laboratory. Clinical Relevance: This tool should enable residency programs to evaluate competency and track individual trainee progress over time.